Analisis Bibliometrik Penelitian Sanitasi Pesantren (2013-2023) - Anwar Firdaus Mutawally; Ayi Budi Santosa; Dadi Mulyadi (Melati Institute, 2023)
This study aims to conduct a bibliometric analysis of sanitation of Pesantren in 2013-2023. The method used is the bibliometric analysis method with the help of Publish or Perish (PoP) and Vosviewer software, while the site studied is Google Scholar. Keyword and metadata validation and also carried out that the visualization can more organized. The results showed that there were 68 journal articles on Islamic boarding school sanitation indexed by Google Scholar, and the development of the theme fluctuated. Some studies also had large citation values. While in terms of visualization, it shows that the research term is still limited, this shows that the pesantren sanitation theme has a huge opportunity to be researched. The solution offered is to increase social-humanities knowledge on pesantren sanitation.